Integrated multi-omics analysis identifies ENY2 as a predictor of recurrence and a regulator of telomere maintenance in hepatocellular carcinoma - Li, Jian-Hua; Tao, Yi-Feng; Shen, Cong-Huan; Li, Rui-Dong; Wang, Zheng; Xing, Hao; Ma, En-Si; Xue, Hong-Yuan; Zhang, Quan-Bao; Ma, Zhen-Yu; Wang, Zheng-Xin (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, and has a high recurrence rate. Accurate prediction of recurrence risk is urgently required for tailoring personalized treatment programs for individual HCC patients in advance. In this study, we analyzed a gene expression dataset from an HCC cohort with 247 samples, and identified five genes including ENY2, GPAA1, NDUFA4L2, NEDD9, and NRP1 as the variables for HCC recurrence prediction. The Cox model and risks score were validated in two public HCC cohorts (GSE76427 and TCGA) and one cohort from Huashan Hospital, which included a total of 641 samples. Moreover, the multivariate Cox regression analysis revealed that the risk score could serve as an independent prognostic factor in the prediction of HCC recurrence. In addition, we found that ENY2, GPAA1, and NDUFA4L2 were significantly upregulated in HCC of the two validation cohorts, and ENY2 had significantly higher expression levels than another four genes in malignant cells, suggesting that ENY2 might play key roles in malignant cells. The cell line analysis revealed that ENY2 could promote cell cycle progression, cell proliferation, migration and invasion. The functional analysis of the genes correlated with ENY2 revealed that ENY2 might be involved in telomere maintenance, one of fundamental hallmarks of cancer. In conclusion, our data indicate that ENY2 may regulate the malignant phenotypes of HCC via activating telomere maintenance.